Unveiling the challenges and opportunities of climate change mitigation through climate-smart agriculture in East Africa, systematic review - Gebremariam Gebrezgabher Gebremedhin; Tsegay Kahsay Gebrekidan; Abraha Kahsay Weldemariam; Niguse Gebru Weldemariam; Daniel Hagos Berhe (International Journal of Climate Change Strategies and Management, 2025)
Purpose – The purpose of this paper is to delve deeply into the challenges and opportunities of adopting climate-smart agriculture (CSA) as a way of dealing with the problems of climate change in the Eastern Africa region. Design/methodology/approach – This review was qualitative in nature and relied on systematic literature review techniques such as searching, data extraction and analysis for determination of the emerging themes regarding challenges, opportunities and best practices in CSA. Findings – This review identifies not only socio-economic disparities, institutional barriers and policy as primary impediments to adopting CSA but also best practices and innovative approaches that prove CSA works. Some of the important ways of dealing with such situations are involvement of all stakeholder, partnerships and knowledge dissemination. In addition, this paper provides a number of relevant suggestions on how best to incorporate CSA at a country and regional level to ensure that the financial and investment strategies are improved. The urgency of accelerating the shifting to climate-resilient agriculture needs to happen much faster, emphasizing the need for proactive measures to ensure food security, livelihoods and environmental integrity. By prioritizing CSA, fostering collaboration and enacting supportive policies, East Africa can navigate the impacts of climate change and build a sustainable agricultural future. Everyone has a role to play in turning these challenges to opportunities and achieving sustainable agricultural development. Originality/value – This review primarily focuses on the most commonly practiced CSA strategies, as examined by various scholars.